Correlation between the Type of Delivery and Intelligence Quotient in Children at 6-7 Years of Age - F Nasiri Amiri (Babol University of Medical Sciences, 2010)
BACKGROUND AND OBJECTIVE: Intelligence can be defined as the ability to assimilate factual knowledge, to recall either recent or remote events, to reason logically, to manipulate concepts, to translate the abstract concepts to the literal concepts and the literal concepts to the abstract concepts, to analyze and synthesize forms. Many factors affect intelligence quotient (IQ). The long-term effects of type of delivery on the intellectual development of children are still not clear. The aim of this study was to determine IQ preschool children based on type of delivery in Babol town, Iran. METHODS: A historical cohort study was conducted on 120 children aged 6-7 years of boys and girls private schools in Babol, Iran during 2004-2007, 60 of those delivered by cesarean section (case group) and 60 spontaneous births (control group) with socioeconomic status, maternal age and parents education status, ranking of birth, weight and age of birth matched. Detailed demographic, medical history and socioeconomic status data were collected by interviewing the mothers and then childrens IQ were administered with Wechsler Preschool and Primary Scales of Intelligence (WPPSI) test by a clinical psychologist and finally the relation between children’s IQ with the type of delivery were determined and compared.FINDINGS: The mean maternal age of case group and control group were 30.18±6.86 and 29.73±5.46 years respectively. The mean age of case group and control group were 6.83± 0.52 and 6.90 ± 0.25 years respectively that there was no significant difference. There was no significant relationship between the type of delivery with total, verbal and performance intelligence quotient. Adjusted mean and standard deviation of full-scale intelligence quotient scores, verbal and performance were 96.53±14.92, 96.87±15.4 and 92.97±13.58 for the case group and 94.07±12.53, 97.10±13.99 and 91.52±13.28 for the control group, respectively. Also no significant differences the sex and full-scale intelligence quotient scores, performance and verbal could be determined.CONCLUSION: The results showed that the type of delivery did not affect children’s intelligence quotient.